Advances and challenges in platelet counting: evolving from traditional microscopy to modern flow cytometry - Chen Yong; Hu Yonggang; Hu Hai (Journal of Laboratory Medicine)
Platelet counting is a fundamental clinical test for diagnosing haemorrhagic diseases, coagulation abnormalities, and certain autoimmune disorders, and it also serves as a critical basis for decisions regarding platelet transfusion. Common automated methods for platelet counting include the international harmonization protocol (IHP) based on flow cytometry, CD61 immunoplatelet count (CD61-imm), impedance platelet count (PLT-I), hybrid platelet count (PLT-H), optical platelet count (PLT-O), and fluorescence platelet count (PLT-F). The IHP, based on flow cytometry, is recommended as the reference measurement procedure (RMP) by the Ministry of Health of the People’s Republic of China, the International Council for Standardization in Hematology (ICSH), and the International Society of Laboratory Hematology (ISLH) due to its superior precision and accuracy. Despite the significant improvements in efficiency and standardization brought about by automation, traditional blood smear microscopic examination (PLT-M) remains indispensable in specific scenarios, such as low platelet counts or abnormal platelet morphology, to ensure the accuracy and reliability of platelet counting results from automated methods.